Pembuatan Aplikasi Showroom Motor “Motoapp” Menggunakan Kodular Dan Airtable Di PT. Tritech Consult Indonesia - Dewi Rosmala; Irsan Rasyidin; Al Fiasyah Arya Lesmana (Lembaga Pengembangan Kinerja Dosen, 2024)
Kodular is a visual application development platform that allows developers to design, create, and publish Android applications without the need for in-depth programming knowledge. It has a number of features that make it an attractive choice for application development projects, especially for beginners and developers who do not have a strong programming background. (www.kodular.com) Airtable is an online database platform that allows users to create databases that are easy to access and manage. It combines the advantages of traditional databases with the freezing and ease of use of spreadsheets. Airtable can be used in a variety of contexts, including business data management, collaborative projects, and application development. (www.airtable.com)